Troll statue in Tromsø's tourist zone - Campbell, Sandy (2024)
This little troll sits outside of a tourist shop near Tromsø's harbour. The troll has a happy expression and exposes his single tooth in a wide smile. He has dark hair, thick dark eyebrows, blue eyes, and oversized ears and nose. His clothing is black and white trimmed with red and green. He has snowshoes attached to his boots and carries a Norwegian flag tied to a stick.